Effects of preweaning and post weaning implants on suckling, growing, and finishing steer performance - D.D. Simms; R.W. Lee; S.B. Laudert; James J. Higgins (Kansas Agricultural Experiment Station Research Reports, 1986)
One hundred and ninety-five crossbred steers were used to compare lifetime implant strategies and study the effects of implanting during the suckling period on performance in the growing and finishing periods. There were no differences in growing period gains when both groups were implanted in the suckling period and the growing period. However, steers implanted in the suckling period but not implanted in the growing period had significantly lower gains than all other treatments including controls. Steers implanted only in the growing period had better feed efficiency in the growing period than both controls and steers implanted only in the suckling period. Steers reimplanted during the finishing period had similar finishing gains regardless of prior implant treatment, and all implanted cattle gained faster than controls in the finishing period. Steers not reimplanted during the finishing period had lower gains than those reimplanted. Implanting in the finishing period resulted in better feed efficiency. All implanted cattle that were reimplanted in the finishing period had higher lifetime gains than controls, but there was no difference between implant combinations. The only carcass characteristic changed by implanting was quality grade, which was reduced by all implant combinations with the exception of implanting only in the finishing period. Implanting during the suckling period did not reduce cattle performance during the growing and finishing periods when the steers were also implanted during these periods. This study emphasizes the importance of implanting twice in the finishing period to maximize finishing gain and final weight.
Keywords: Cattlemen' s Day; 1986; Kansas Agricultural Experiment Station contribution; no. 86-320-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 494; Beef; Implants; Suckling; Growth; Steer performance